Mutation in the STXBP1 Gene Associated with Early Onset West Syndrome: A Case Report and Literature Review - Kanako Takeda; Yusaku Miyamoto; Hisako Yamamoto; Toshiyuki Iwasaki; Noriko Sumitomo; Eri Takeshita; Atsushi Ishii; Shinichi Hirose; Naoki Shimizu (MDPI AG, 2022)
Syntaxin-binding protein1 (STXBP1) is a member of the Sec1/Munc18-1 protein family, which comprises important regulators of the secretory and synaptic vesicle fusion machinery underlying hormonal and neuronal transmission, respectively. STXBP1 pathogenic variants are associated with multiple neurological disorders. Herein, we present the case of a Japanese girl with a mutation in the STXBP1 gene, who was born at 40 weeks without neonatal asphyxia. At 15 days old, she developed epilepsy and generalized seizures. Around 88 days old, she presented with a series of nodding spasms, with the seizure frequency gradually increasing. Interictal EEG indicated hypsarrhythmia and she presented with developmental regression. At 1.5 years old, genetic testing was performed and mutational analysis revealed an STXBP1 gene mutation (c.875G > A: p.Arg292His). Accordingly, she was diagnosed with developmental and epileptic encephalopathy, presenting West syndrome's clinical characteristics caused by the STXBP1 gene mutation. Although drug treatment has reduced the frequency of epileptic seizures, her development has remained regressive. The relationship between the location and type of genetic abnormality and the phenotype remains unclear. Future studies should investigate the genotype-phenotype correlation and the underlying pathophysiology to elucidate the causal relationships among the multiple phenotype-determining factors.